2021
DOI: 10.3389/fimmu.2021.747335
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation Between Fibroblasts and T Cells in Fibrosing Interstitial Lung Diseases

Abstract: Interstitial lung diseases (ILDs) are a heterogeneous group of diseases characterized by varying degrees of inflammation and fibrosis of the pulmonary interstitium. The interrelations between multiple immune cells and stromal cells participate in the pathogenesis of ILDs. While fibroblasts contribute to the development of ILDs through secreting extracellular matrix and proinflammatory cytokines upon activation, T cells are major mediators of adaptive immunity, as well as inflammation and autoimmune tissue dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 131 publications
(122 reference statements)
0
11
0
Order By: Relevance
“…Lung myofibroblasts are heterogeneous in terms of their origins. The predominant sources of myofibroblasts are resident fibroblasts (lipofibroblasts, matrix fibroblasts, and alveolar niche cells) and pericytes (residing within basal membranes or perivascular linings), along with minor sources such as hematopoietic CXCR4+ fibrocytes, alveolar epithelial cells (AECs), endothelial cells (ECs), and mesenchymal stem cells (MSCs) [ 98 ]. Under the influence of environment-specific factors, cytokines, such as TGF-β, fibroblast-to-myofibroblast transition/transdifferentiation (FMT) changes lung resident fibroblast behavior/phenotypes to another type of normal differentiated cell and the downstream effects at the tissue level [ 99 ].…”
Section: Dna Methylation In Fibrosismentioning
confidence: 99%
“…Lung myofibroblasts are heterogeneous in terms of their origins. The predominant sources of myofibroblasts are resident fibroblasts (lipofibroblasts, matrix fibroblasts, and alveolar niche cells) and pericytes (residing within basal membranes or perivascular linings), along with minor sources such as hematopoietic CXCR4+ fibrocytes, alveolar epithelial cells (AECs), endothelial cells (ECs), and mesenchymal stem cells (MSCs) [ 98 ]. Under the influence of environment-specific factors, cytokines, such as TGF-β, fibroblast-to-myofibroblast transition/transdifferentiation (FMT) changes lung resident fibroblast behavior/phenotypes to another type of normal differentiated cell and the downstream effects at the tissue level [ 99 ].…”
Section: Dna Methylation In Fibrosismentioning
confidence: 99%
“…For example, lung and oesophageal fibroblasts are responsive to LIGHT and IL-13, which can be secreted by CD4+ T cells in asthma or EoE (Antunes et al, 2018;Wen et al, 2019). On the other hand, the ability of fibroblasts to modulate T or B cell responses may be an important factor in RA, ILD and skin inflammation, amongst other diseases (Lai et al, 2021;Tu et al, 2022;Xu et al, 2022). In their cross-tissue fibroblast analysis, Korsunsky et al (2022) reported a cluster of inflammatory fibroblasts that are common to lung, intestine, joints and salivary glands and found that these cells express CXCL10 and CCL19.…”
Section: Leukocytesmentioning
confidence: 99%
“…In addition to these chemokine‐mediated interactions, fibroblasts may also have contact‐dependent interactions mediated by antigen cross‐presentation. Naïve T cells may sense antigens presented by fibroblasts via a major histocompatibility class I/II and ICAM‐1‐dependent mechanism, whereas T cells can stimulate RA‐fibroblasts to produce inflammatory cytokines via membrane‐bound TNF and CD40L/α5β1 integrin (Lai et al., 2021; Lochhead et al., 2020). Fibroblasts may contribute to the differentiation and activation of B cells in RA through production of IL‐6, VCAM‐1, CXCL12 and TNFSF13B/B cell activating factor (Nygaard & Firestein, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it will be very useful to know whether tacrolimus can replace the age-honored therapeutic scheme of cyclophosphamide as induction followed by azathioprine maintenance treatment in ILD associated with CTD. 1 Because T cells are thought to play a key role in driving and maintaining not only muscle inflammation, but also myositis-related ILD, 10 tacrolimus as a potent T cell inhibitor is particularly well poised to hold promise to replace the more toxic CYC as therapeutic agent of choice.…”
Section: Drugs Already In Current Use For Myositismentioning
confidence: 99%